Relationship between Selected Cephalometric Parameters, Nasolabial Angle and Its Components in Adolescent Females - Mikołaj Gołębiowski; Agnieszka Świątkowska; Przemysław Pastuszak; Mansur Rahnama (Diagnostics, 2023)
Nasolabial angle is commonly used to assess the soft tissue profile of the subnasal region. The aim of this retrospective study was to evaluate the relationship between the nasolabial angle, the inclination of the lower border of the nose and upper lip, upper incisor inclination and upper lip thickness. A sample of 142 female adolescents aged 13–18 years was chosen. A modified cephalometric analysis was performed with the nasolabial angle, and its components were traced according to Fitzgerald’s method. All analysed parameters showed a statistically significant correlation with the nasolabial angle (NLA). The highest correlation was found for the labial (L/FH) and nasal (N/FH) components of the nasolabial angle, respectively. Upper incisor inclinations (1+:SN, U1FA) and upper lip thickness (ULT) had a stronger correlation with L/FH than NLA, but no correlation was found between these parameters and N/FH. Upper lip thickness did not influence the relationship between incisor inclination and NLA or L/FH. The position of the upper incisors and upper lip thickness influence the nasolabial angle indirectly through its labial component (L/FH). Therefore, it seems purposeful to assess the nasolabial angle as a sum of two independent angles, of which only one (L/FH) can be influenced by orthodontic treatment.